2005
DOI: 10.1177/0272989x04268956
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically Based Discrete-Event Simulation of End-Stage Liver Disease and the Organ Allocation Process

Abstract: The authors created a discrete-event simulation model that represents the biology of end-stage liver disease and the health care organization of transplantation in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 10 publications
0
77
0
1
Order By: Relevance
“…One of the first papers in this vein is by Ruth et al (1985), in which the authors develop a simulation model to study the problem. Shechter et al (2005) also introduce a discrete event simulation model for the evaluation of potential changes to the liver allocation process. In this work, we utilize the simulation model developed by the SRTR, see KPSAM (2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the first papers in this vein is by Ruth et al (1985), in which the authors develop a simulation model to study the problem. Shechter et al (2005) also introduce a discrete event simulation model for the evaluation of potential changes to the liver allocation process. In this work, we utilize the simulation model developed by the SRTR, see KPSAM (2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simulation modeling has been used to study a wide range of problems in health care [13,15,29,35,45]. In recent years, Zenios et al [51], Kreke et al [31], and Shechter et al [44] utilized simulation models even to study organ allocation systems. A comprehensive review of health care simulation models can be found in Klein et al [30] and Jun et al [27].…”
Section: Simulation-optimization Modelsmentioning
confidence: 99%
“…Simulation modeling has been used to study a wide range of problems in health care [15,17,28,34,46]. In recent years, Zenios et al [52], Kreke et al [31], and Shechter et al [41] utilized simulation models to study organ allocation systems. A comprehensive review of health care simulation models can be found in Klein et al [30] and Jun et al [27].…”
Section: Simulation Modeling In Health Carementioning
confidence: 99%